0085 Helping Managers Manage: Simulation Is Critical To Success. (1st November 2014) - Mardon, Irene; Hamilton, Carrie
Abstract : Context: Building on the belief that simulation is an effective way to learn clinical and examination skills, University Hospital Southampton (UHS) believed that simulation could be an effective way to help managers learn skills that they are often expected to 'just do'. Managers in health care are often expected to undertake these roles without formal training, 1 sometimes with an adverse outcome. We wanted to assist the managers within our organisation to: mediate and resolve disputes and conflicts between staff members conduct investigations into grievances about staff members Methodology: Based on real life situations of disputes and grievances that commonly take place within organisations, scenarios were drafted by the human resource team and reviewed by the simulated patient programme lead. Examples of investigation scenarios were: theft from the organisation, use of non work internet at work, visiting a patient at home. Simulated patients – although in this case, they were simulated health care professionals – were then trained to take on the role of the staff member and trained in 'organisational culture'. Managers were invited to attend whole day training for each of the two areas of management; dispute mediation and investigation. Outcomes: Successful courses have been run for over 100 managers, using simulated staff members. Skills of either mediation between two staff members, or investigation of a grievance have been practised in a safe learning environment. Evaluations have been overwhelmingly positive, with staff members consistently stating that these are critical skills for any health care manager. Conclusion: With collaborative working, human resource departments and simulated patient programmes can work together to ensure that managers are skilful in mediating disputes and investigating grievances. This important experiential training will arm managers with skills that will enable them to retain staff, resolve issues, follow correct procedures and save money. Reference: Marcus LJ, Dorn BC, McNulty EJ. Renegotiating health care: Resolving conflict to build collaboration. John Wiley & Sons, 2011